When You Are Hurt, Does It Bleed? - Agustin, Christopher (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2026)
Pain, whether physical or emotional, reflects the struggles that shape human existence. Wounds and scars symbolize suffering, healing, and resilience, revealing how adversity contributes to personal growth and self-discovery. Despite life’s hardships, hope and strength emerge, allowing individuals to move forward with greater compassion and understanding.